Work on the mountain - González, N. V. M., 1915-1999.; Guzman, Richard R. (Diliman, Quezon City : University of the Philippines Press, 1995)
Criticism on Philippines literature.
With: As in myth, the signs were all over / by Richard R. Guzman.
Includes bibliographical references.
Keywords: Philippine literature (English) -- 20th century -- History and criticism